(untitled) (Research, Society and Development, 2020)
The objective of this study was to verify whether the management of health service waste-RSS in a state public hospital was in accordance with he current rules, analyzing the potential and weaknesses. The exploratory research took place in a large hospital (292 beds and 186 visits / day), in Campina Grande, Paraíba state, Brazil. It was found that the daily average production of RSS is 1,122.4 kg. The characteristics of this waste require care from generation to final disposal and demonstrate that even in a hospital of this size that attends to emergencies, urgencies and traumas, most of the waste generated is not infectious or sharp. Of the total generated, 60.36% were common waste (D), 21.96 %% infected waste (A), 11.96% recyclable and 5.72% sharps (E).Despite being the first hospital in the municipality to implement the RSS Management Plan, weaknesses were identified in the different stages, especially in relation to segregation at the generating source, the maintenance, identification and acquisition of collectors with volumetric capacity in line with the generation of sector; the maintenance and inspection of the temporary storage location and the implementation of environmental education programs and projects for the social actors involved. The hospital studied, although it has an RSS Management Plan, presents weaknesses that require solutions to avoid and / or mitigate negative environmental, social and economic impacts and to reduce the probabilities of materialization of the dangers in herent to these residues, especially with regard to the health of employees, students, interns, patients, companions, recyclable material collectors and the surrounding population.